2023
DOI: 10.1002/jeab.830
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcer pathology, probabilistic choice, and medication adherence in patients with multiple sclerosis

Abstract: The reinforcer pathology model posits that core behavioral economic mechanisms, including delay discounting and behavioral economic demand, underlie adverse health decisions and related clinical disorders. Extensions beyond substance use disorder and obesity, however, are limited. Using a reinforcer pathology framework, this study evaluates medical adherence decisions in patients with multiple sclerosis. Participants completed behavioral economic measures, including delay discounting, probability discounting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, people may perceive relatively mild STIs like chlamydia and gonorrhea as non-serious, unurgent, or unimportant, and consequently be more susceptible to the inconvenience and unpleasantness of waiting. Further, because the rates of discounting can be affected by the amount or size of the outcomes (Green & Myerson, 2004 ; Jarmolowicz et al, 2023 ), the perceived values of testing for chlamydia and gonorrhea might be low in the first place, resulting in higher degrees of discounting. However, even nonlethal STIs can cause serious and permanent health damage if left untreated (e.g., infertility) (Hull et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, people may perceive relatively mild STIs like chlamydia and gonorrhea as non-serious, unurgent, or unimportant, and consequently be more susceptible to the inconvenience and unpleasantness of waiting. Further, because the rates of discounting can be affected by the amount or size of the outcomes (Green & Myerson, 2004 ; Jarmolowicz et al, 2023 ), the perceived values of testing for chlamydia and gonorrhea might be low in the first place, resulting in higher degrees of discounting. However, even nonlethal STIs can cause serious and permanent health damage if left untreated (e.g., infertility) (Hull et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The delay discounting approach has also been used to examine medical decision making. For example, steeper delay discounting for monetary rewards was associated with lower adherence to medication procedures in patients with multiple sclerosis (Jarmolowicz et al, 2023 ). Regarding testing decisions, one study found that testing intentions for COVID-19 decreased as the delay to receiving the test or its results increased (Strickland et al, 2022 ).…”
mentioning
confidence: 99%